Fitness to Stand Trial in One Australian Jurisdiction: The Role of Cognitive Abilities, Neurological Dysfunction and Psychiatric Disorders. Issue 4 (3rd July 2016) - White, Amanda Jane; Batchelor, Jennifer; Meares, Susanne; Pulman, Susan; Howard, Dan
Abstract : In Australia, limited research of the factors determining fitness to stand trial (FST) has been conducted. In particular, the relevance of cognitive abilities and neurological dysfunction in accordance with the legal standard of R v. Presser (1958) has not been comprehensively explored. In the largest known sample of court-determined FST cases in Australia examined to date, expert reports for 153 unfit and 91 fit defendants in New South Wales (NSW) over a five-year period were retrospectively reviewed. Data related to cognitive assessment, psychiatric disorders, neurological dysfunction, demographic factors and expert opinion were extracted. The results showed that cognitive abilities, in particular verbal memory, nonverbal skills, and executive functioning, were influential in differentiating between fit and unfit groups and determining FST. However, quantitative analysis was limited as few reports contained test scores or comprehensive psychometric analysis. Defendants with neurological dysfunction alone or with a dual diagnosis of a psychiatric disorder or intellectual disability were more likely to be found unfit to stand trial. Expert opinion was biased toward the referring agent and psychologists were less likely than psychiatrists to examine all of the relevant legal criteria. Comprehensive cognitive assessment in specific cases and more standardised assessment practices are indicated.